Rajasthan Enacts a Soil Conservation Legislation - singh, Ranbir (Journal of Soil and Water Conservation, 2022)
Soil & Water Conservation pro-gramme was started in Rajasthan in the year 1957-58. The programme made its beginning in 8 Districts of Rajasthan and it gradually spread to 20 Districts by the year 1965-66. The total programme was taken up through extension methods involving tremendous persuasive efforts, education and propo-ganda which meant considerable time lags between initial contacts with the farmers and actual treatment of land.